2016
DOI: 10.1016/j.jsv.2015.12.031
|View full text |Cite
|
Sign up to set email alerts
|

Equivalent modulus method for finite element simulation of the sound absorption of anechoic coating backed with orthogonally rib-stiffened plate

Abstract: The finite element method is often used to investigate the sound absorption of anechoic coating backed with orthogonally rib-stiffened plate. Since the anechoic coating contains cavities, the number of grid nodes of a periodic unit cell is usually large. An equivalent modulus method is proposed to reduce the large amount of nodes by calculating an equivalent homogeneous layer. Applications of this method in several models show that the method can well predict the sound absorption coefficient of such structure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Particularly, the equivalent homogenous layer is extended and compressed longitudinally due to the gradually varied displacement amplitudes. These phenomena provide an intuitive understanding of the vibration pattern of the lumped spring-mass oscillator model for the metasurface/steel plate system 4648,55 , in which the mass is offered by the steel plate and the rubber metasurface plays the role of spring with proper damping. The embedded cavities are utilized to adjust the effective stiffness of the rubber matrix into the required one.…”
Section: Resultsmentioning
confidence: 96%
“…Particularly, the equivalent homogenous layer is extended and compressed longitudinally due to the gradually varied displacement amplitudes. These phenomena provide an intuitive understanding of the vibration pattern of the lumped spring-mass oscillator model for the metasurface/steel plate system 4648,55 , in which the mass is offered by the steel plate and the rubber metasurface plays the role of spring with proper damping. The embedded cavities are utilized to adjust the effective stiffness of the rubber matrix into the required one.…”
Section: Resultsmentioning
confidence: 96%
“…Due to the periodic arrangement of the structure, the displacement and the acoustic pressure satisfy the periodic condition in x direction, which can be expressed as [24]:…”
Section: Theory Of the Finite Element Method(fem)mentioning
confidence: 99%
“…An equivalent modulus method based on impedance transfer formula was proposed, which reduced the number of calculating nodes. The study indicated that an increase in the mass of backing caused absorption peak to move to low frequency [47], as shown in Figure 10.…”
Section: Overall Design On Acoustic Coatingsmentioning
confidence: 99%
“…Acoustic radiation of underwater cylindrical shells. Calculating model of a unit cell, its top view, and absorption coefficients of the Alberich anechoic coating backed with different steel plates [47]. …”
Section: Figurementioning
confidence: 99%